Safety and efficacy of the novel surgical dye from blue butterfly pea flower: an ex vivo and in vitro study - Khotcharrat, Rossukon; Thongsuk, Wanachat; Paensuwan, Pussadee (Chulalongkorn Medical Journal, 2022)
Background: The chemical dyes were used for anterior capsule staining with caution. There is no natural dye available. The extract from traditional Thai herb may be an alternative dye. Objectives: To assess the in vitro cytotoxicity of the novel surgical dye on corneal endothelial cells and evaluate the proper concentration for staining on anterior lens capsule during cataract surgery in ex vivo. Methods: Safety of the dye in various concentrations on human corneal endothelial cell line was evaluated by resazurin technique. The efficacy of human anterior capsular staining at different concentrations of the dye and different time-points was also studied under an operative microscopic camera recorder. Results: The cytotoxicity test showed no significant viability loss at any concentration. The ex vivo tests on 20 pieces of human anterior capsules were arranged in 5 sets and exposed to 4 different concentrations of the dye at various times. The concentration of 500 - 1,000 mg/ml provided better staining than the 200 mg/ml concentration, while the concentration of 40 mg/ml solution gave a negative stain. Conclusion: The novel surgical dye from butterfly pea flower extract was successfully developed. The dye solution exhibited non-toxic to corneal endothelial cells and showed suitable for anterior lens capsule staining. Overall, it could be an alternative for safe staining of the anterior lens capsule in cataract surgery.